An Integrated Approach Involving EMO and HYDRUS-2D Software for SWRT-based Precision Irrigation - (:unkn) unknown (IEEE, 2015)
Retaining water at the root level of crops has been a major focus in precision irrigation system from technological, societal, and environmental points of view. Subsurface water retention technology (SWRT) through impermeable membranes placed at certain depths under has shown 1.4 to 3.4-fold increase in production in crops. However, the sizing, placement and surface water scheduling are important parameters for achieving an optimal yield. In this paper, for the first time, we consider a water flow simulation model through soil (HYDRUS-2D) which is integrated with an evolutionary multi-objective optimization (EMO) algorithm to find optimal membrane configurations and surface water supply under multiple conflicting objectives. The initial results presented in this paper clearly demonstrate the merit of such a collaboration and supports further studies. Not only the integrated approach finds optimal membrane configurations and water supply, but also reveals a number of useful insights and knowledge about optimal precision irrigation, a matter which has long term contributions to water conservation, ground-water preservation, and many natural resources directly affecting modern society.